KONSELING, INFORMASI, DAN EDUKASI KESEHATAN REPRODUKSI PADA REMAJA - Regina Pricilia Yunika; Recta Olivia Umboro; Fitri Apriliany; M. Zulfikar Al Fariqi (Stikes Yarsi Mataram, 2022)
Adolescence is a period of transition, and tends to want to try new things so that it can have a negative impact on adolescents. Lack of knowledge related to reproductive health can cause reproductive health problems for adolescents. It is believed that improving the degree of reproductive health to change behavior in order to live a healthy life can be done by providing reproductive health education. Understanding and information on reproductive health is very much needed at this phase and education can be done through the provision of counseling or which includes material about the changes that occur when entering adolescence. The purpose of this activity is to educate young people regarding reproductive health issues. The method of implementing this community service activity was carried out on productive age teenagers at SMA Negeri 2 Mataram, due to limited space and the obligation to apply health protocols. The participants of this activity were represented by 25 students who were selected based on membership in theYouth Red Cross (PMR) extracurricular and the School Health Unit. (UKS). This activity is carried out with the mechanism of counseling, information, education, through health promotion media in the form of leaflets and counseling. Accurate information related to adolescent's concern for their reproductive health. The majority of SMA Negeri 2 Mataram students still think that reproductive health is something they do not fully understand. For this reason, they need to be given information to better understand reproductive health. In conclusion, providing education to adolescents about reproductive health can increase the knowledge and understanding of adolescents about the reproductive system. The PKM team evaluates what has been conveyed by asking the youth to mention a healthy reproductive system. This activity provides benefits for students of SMA Negeri 2 Mataram who previously did not know about good reproductive health to better understand their reproductive health.